2020
DOI: 10.4103/jfmpc.jfmpc_153_20
|View full text |Cite
|
Sign up to set email alerts
|

A study on effect of yoga on emotional regulation, self-esteem, and feelings of adolescents

Abstract: Background: The present study has investigated the effect of yoga on the emotional regulation, self-esteem, and feelings of the adolescents. Methods: The participants of the study are 110 students aged 13–18 years and studying in the senior secondary schools of Mandi district (Himachal Pradesh). The sample consisted of 52 adolescents practicing yoga and 58 adolescents who have never practiced yoga. The primary data has been collected through standardized instruments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A systematic review conducted in 2020 by Wei-Li Wang et al, concluded that to manage sleep problems yoga could be more beneficial than non-active people (19) . Similarly, other studies prove yoga to be effective to improve the self-esteem and quality of life of yoga practitioners (20,21) . Our study findings are also in line with the previous evidence however in the present study participants were overweight or obese and were compared with the active group.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…A systematic review conducted in 2020 by Wei-Li Wang et al, concluded that to manage sleep problems yoga could be more beneficial than non-active people (19) . Similarly, other studies prove yoga to be effective to improve the self-esteem and quality of life of yoga practitioners (20,21) . Our study findings are also in line with the previous evidence however in the present study participants were overweight or obese and were compared with the active group.…”
Section: Resultsmentioning
confidence: 82%
“…Increased weight, getting out of shape, and difficulty in performing the daily activities could directly lead to impaired quality of life. It can also cause psychological stress and this difficulty to regulate emotions can lead to low self-esteem which is commonly present in obese people (23) . A study conducted by Hyunwoo Kang et al, in 2021 showed that mindfulness yoga improves self-esteem and can be used as an alternative treatment strategy to manage psychological issues in middle-aged men (24) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga Nidra is a meditation technique including muscle relaxation, breathing practices, imagination, and resolve-making, which provides deep relaxation and experimentally has been proven to reduce stress levels (21). There are multiple pieces of evidence of improving self-esteem starting from school students (22), adolescents (23), university students (24), and middleaged women (25) life after introducing the yoga module as an intervention. The practice of a holistic approach to Yoga, including physical practices (asanas) associated with breathing practices (pranayamas) and meditation techniques, has a definite correlation with positive self-esteem and enhanced psychological well-being (26).…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is considered to be easy to practice for children and adults of all ages. Yoga has also been shown to be effective in improving self-esteem, emotional well-being, positive emotions, and selfregulation in adolescents (22). In several meta-analyses, yoga interventions have been proven to be effective for treating fatigue, pain, hypertension, and type II diabetes (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%